EKSISTENSI MADRASAH DALAM PENDIDIKAN INDONESIA - Susilawati, Samsul (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2008)
The existence of madrasah in developing an education at Indonesia is very important, despite of many people consider that madrasah is a second institution in Indonesia of other education institution. However Madrasah be able to survive to develop an education in Indonesia, even Madrasah contribute to release the excellent graduations, and whose is able to glorify the Indonesia, especially in education aspect.Keywords: Madrasah and Education Â Â  Â